Effect of Climatic Fluctuations on Post-Fire Regeneration of Two Jack Pine and Red Pine Populations during the Twentieth Century - Bergeron, Yves; Brisson, Jacques (Géographie physique et Quaternaire, 1994)
ABSTRACTThe age structure of two mixed red pine (Pinus resinosa Ait.) and jack pine (Pinus banksiana Lamb.) forests located at Lac Duparquet, northwestern Québec, were correlated with mean annual temperature and total precipitation recorded at Iroquois Falls for the period between 1913 and 1986. The age structures of both pine species showed a common pattern of regeneration characterized by low regeneration before 1930, an important regeneration peak starting around the 1930s, a dip in the age structure around 1950, a second, though less important, regeneration peak in the 1960s, and an important drop, especially for red pine, after 1970. In general, high regeneration rates were positively correlated with precipitation and negatively with temperature, suggesting that pine recruitment is negatively affected by low snow cover and/or drought. The absence of correlation with temperature suggests that the red pine northern limit may be controlled more by a change in the fire regime than by increasing temperature.